IMPLEMENTASI PERMAINAN MENYUSUN KATA DALAM UPAYA MENINGKATKAN KEMAMPUAN BERBICARA BAHASA INGGRISSISWA KELAS VIIIA SMPN 3 TAMPAKSIRING TAHUN PELAJARAN 2020/2021 - Ni Nyoman Martini (WACANA : MAJALAH ILMIAH TENTANG BAHASA, SASTRA DAN PEMBELAJARANNYA, 2022)
The implementation of the arranging words game in order to increase the students speaking abillities. The subjects of this research was the students of VIIIASMPN 2 Tampaksiring in the first semester of the academic year of 2020/2021. The writter choose this class because there were so many students still have less abilities in English, especially in speaking skill. The main purpose of this research is increasing students speaking abillities by the implementation a new teaching learning model. The data collecting methode is learning achievement test.The data analyze is descriptive to qualitative and quantitative data.The research revealed that The implementation of the arranging words game in order to increase the students learning achievement.We can see the students achievement can increase from the early cycle to the first cycle and to the second cycle.Finally,It can be concluded that the implementation of the arranging words game can increase the students achievement. Key words: Speaking Abillities, Cooperative Learning, Arranging Words Game